2022
DOI: 10.1093/botlinnean/boab105
|View full text |Cite
|
Sign up to set email alerts
|

Niche conservatism, divergence and polyploidy inSennaseriesAphyllae(Fabaceae: Caesalpinioideae) from arid zones of South America

Abstract: This paper aims to integrate cytogenetic and ecological approaches into a phylogenetic framework to better understand the evolution and systematics of Senna series Aphyllae, an endemic group of arid and semi-arid regions of South America. We counted the chromosome numbers at the population level in three species of series Aphyllae using a conventional technique (GIEMSA) and in situ hybridization (FISH). Phylogenetic reconstructions and inference of chromosome evolution were based on four plastid DNA regions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…The chromosomal variation, encompassing dysploidy and polyploidy with chromosome numbers of 2n = 26, 28, 48, and 56, observed in the four Senna species investigated here was consistent with previous reports (Souza and Benko-Iseppon, 2004;Rice et al, 2015;Robbiati et al, 2022). However, our study revealed an intriguing correlation FISH Mapping of Four Senna Species Revealing Genome Dynamics during Species Diversification of the Genus between the chromosomal variation in this case and rearrangements of ribosomal DNA and telomeric repeat sites in…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The chromosomal variation, encompassing dysploidy and polyploidy with chromosome numbers of 2n = 26, 28, 48, and 56, observed in the four Senna species investigated here was consistent with previous reports (Souza and Benko-Iseppon, 2004;Rice et al, 2015;Robbiati et al, 2022). However, our study revealed an intriguing correlation FISH Mapping of Four Senna Species Revealing Genome Dynamics during Species Diversification of the Genus between the chromosomal variation in this case and rearrangements of ribosomal DNA and telomeric repeat sites in…”
Section: Discussionsupporting
confidence: 92%
“…Two 5S rDNA signals were detected in all diploids, whereas tetraploids had four signals. However, an increase in 5S rDNA signals was observed in two diploid Senna species with x = 12: S. pachyrrhiza and S. uniflora, each exhibiting three to four chromosomes bearing 5S rDNA signals, (Nguyen et al, 2021;Robbiati et al, 2022).…”
Section: Sennamentioning
confidence: 96%
See 3 more Smart Citations